(untitled) (Journal of the College of Education for Women, 2019)
The study found a number of results. The most prominent were the low married during the years of the study in 1997-2012. The study also showed the level of administrative units that the percentage of widows and single rise in urban and rural decline. This is due to the different nature of urban and rural society of the behavior and social habits and traditions.As the proportion of divorced and unmarried are decreased in urban and increase proportion in the countryside, and this is due to the influence of the rural population in the urban centers. As well as the study showed that there was a significant effect of the economic and social factors and other factors on marital status on its parts in the study area.